BIOLOGICAL ACTIVITY OF FERNS OF THE BURYAT REPUBLIC - V. M. Shishmarev; T. M. Shishmareva (Acta Biomedica Scientifica, 2017)
The Buryat Republic has a diverse and rich flora which includes many valuable ornamental, medicinal and food plants. These plants include the representatives of the division of ferns (Polypodiophyta) related to one of the most ancient groups of higher plants. Ferns are used in Tibetan, Chinese and Indian medicine, as well as by the inhabitant of the Caucasus, Eastern Himalayas, North America and others. On the territory of the Buryat Republic 25 species of medicinal ferns are identified. The data on the medicinal ferns of the Buryat Republic and their biological activity is systematized in this review. The results of experimental studies of various dosage forms and the extracts from the individual components isolated from different parts of the ferns (roots and rhizomes, fronds, stalks, gametophytes, disputes) are presented in detail. The generalization of literature data shows that rather small number of medicinal ferns of the Buryat Republic has broad spectrum of biological activity.